Effect of foliar spray of nano urea and 2% urea on growth parameters which contribute to yield of safflower: Effect of foliar spray of nano urea and 2% urea on growth parameters which contribute to yield of safflower - P A GAYATHRI; S B GHUGE; S A SHINDE (Journal of Oilseeds Research, 2023)
The results from the present investigation showed that application of 100% nitrogen in the form of urea top dressing at vegetative stage and foliar spray of nano urea and 2% urea at reproductive stage improved the physiological parameters and yield of safflower. The growth parameters viz. leaf area index, relative growth rate, crop growth rate and net assimilation rate and seed yield recorded maximum values with 100% N application, while they reduced when the nitrogen dose was halved.